FLT3 ligand regulates expansion of regulatory T-cells induced by regulatory dendritic cells isolated from gut-associated lymphoid tissues through the Notch pathway - Na Li; Jingwei Mao; Haiying Tang; Xiaoyan Tan; Jian Bi; Hao Wu; Xiuli Chen; Yingde Wang; Yuanyuan Ji (Chinese Medical Journal)
Abstract. Background:. Regulatory dendritic cell (DCreg) subset exhibits a unique capacity for inducing immune tolerance among the variety subsets of dendritic cells (DCs) within gut-associated lymphoid tissues (GALTs). Fms-like tyrosine kinase 3 ligand (FLT3L) is involved in the differentiation of DCregs and the subsequent expansion of regulatory T-cells (Tregs) mediated by DCregs, though the precise mechanism remains poorly understood. This study aimed to explore the expansion mechanism of Treg induced by DCreg and the role of FLT3L in this process. Methods:. DCregs were distinguished from other DC subsets isolated from GALTs of BALB/c mice through a mixed lymphocyte reaction assay. The functions and mechanisms by which FLT3L promoted Treg expansion via DCregs were investigated in vitro through co-culture experiments involving DCregs and either CD4+CD25− T-cells or CD4+CD25+ T-cells. Additionally, an in vivo experiment was conducted using a dextran sulfate sodium (DSS)-induced colitis model in mice. Results:. CD103+CD11b+ DC exhibited DCreg-like functionality and was identified as DCreg for subsequent investigation. Analysis of Foxp3+Treg percentages within a co-culture system of CD4+CD25− T-cells and DCregs, with or without FLT3L, demonstrated the involvement of the FLT3/FLT3L axis in driving the differentiation of precursor T-cells into Foxp3+ Tregs induced by DCregs. Cell migration and co-culture assays revealed that the FLT3/FLT3L axis enhanced DCreg migration toward Tregs via the Rho pathway. Additionally, it was observed that DCregs could promote Treg proliferation through the Notch pathway, as inhibition of Notch signaling by DAPT (N-[N-(3,5-difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester) suppressed Treg expansion within the co-culture system of DCregs and CD4+ T-cells or CD4+CD25+ T-cells. Furthermore, the FLT3/FLT3L axis influenced JAG1 expression in DCregs, indirectly modulating Treg expansion. In vivo experiments further established that FLT3L promoted DCreg expansion and restored Treg balance in DSS-induced colitis models, thereby ameliorating colitis symptoms in mice. Conclusion:. The FLT3/FLT3L axis is integral to the maintenance of DCreg function in Treg expansion.